Three-dimensional geometric morphometric study of the Xuchang 2 cranium. Issue 178 (May 2023) - Zhang, Yameng; Li, Zhanyang
Abstract: Results of traditional metric and nonmetric assessments suggest that the Xuchang hominin shares features with Neanderthals. To comprehensively compare the nuchal morphology of XC 2 to those of the genus Homo, we conduct a three-dimensional geometric morphometric study with 35 cranial landmarks and surface semilandmarks of XC 2, Homo erectus, Middle Pleistocene humans, Neanderthals, and early and recent modern humans. Results reveal that the centroid size of XC 2 is larger than that of early and recent modern humans and can only be compared to that of Middle Pleistocene humans and H. erectus . Early and recent modern humans share a nuchal morphology distinct from archaic hominins (Ngandong H. erectus, Middle Pleistocene humans, and Neanderthals), except for SM 3, Sangiran 17, and Asian and African H. erectus . Although Ngandong specimens differ from the other H. erectus, it is unclear whether this represents a temporal or spatial trend in the process of evolution of this species. The nuchal morphological resemblance between Middle Pleistocene humans and Neanderthals may be attributed to similar cranial architecture and cerebellar shape. The great nuchal morphological variation shared by recent modern humans may indicate a particular developmental pattern. In conclusion, the nuchal morphology of different human groups is highly variable and may be caused by different factors including brain globularization and developmental plasticity. XC 2 shares similar nuchal morphology with Middle Pleistocene humans and Neanderthals, but these results are insufficient to fully resolve the taxonomic status of XC 2.